Evaluasi Faktor yang Memengaruhi Usability Aplikasi Thymun Menggunakan Structural Equation Model-Partial Least Square - Rahma Dany Asyifa; Agus M Soleh; Bagus Sartono (Xplore: Journal of Statistics, 2021)
Application development must be done by considering the usability factor of the application. Three aspects of usability measurement, namely usefulness, satisfaction, and ease of use, are latent variables that cannot be measured directly, so the appropriate analysis is the Structural Equation Model-Partial Least Square (SEM-PLS). PLS is a SEM analysis approach that does not require assumptions of data distribution and a minimum number of observations. The measurement of the usability of the Thymun application is described in two SEM-PLS models. This study aims to determine the best model and determine the effect of usefulness, satisfaction, and ease of use on the usability of the Thymun application. The data used is survey data to 44 Thymun application users. The sampling technique used was purposive sampling. The results showed that the best model has a good measure with an R-square value of 0.730 and Q2 0.453 with a Goodness of Fit 0.736. The variables of usefulness and ease of use have a significant effect on the 5% real level with path coefficient values ​​of 0.255 and 0.636. While the satisfaction variable does not have a significant effect on the 5% real level with a path coefficient of 0.058. Thymun application usability score is 76.47.